1999
DOI: 10.1159/000051451
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthetic Anti-Acute Pancreatitis Agent, IS-741

Abstract: A novel synthetic drug, IS-741, inhibited cell adhesion in vitro and neutrophil in vivo. Thus, IS-741 inhibited the magnification of pancreatic lesion as well as progression to multiple organ failure in acute pancreatitis models. Furthermore, IS-741 at identical plasma concentrations equally improved the survival rates in animals of various species with severe acute pancreatitis. Based on these observations, it was considered that IS-741 inhibited tissue destruction by neutrophil after inhibiting neutrophil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It has also been reported that the inhibition by IS-741 of leukocyte infiltration is based on inhibition of cell adhesion (22,23). IS-741 acts on HL-60 (a human promyelocytic leukemia line) and inhibits the adhesion of HL-60 to vascular endothelial cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the inhibition by IS-741 of leukocyte infiltration is based on inhibition of cell adhesion (22,23). IS-741 acts on HL-60 (a human promyelocytic leukemia line) and inhibits the adhesion of HL-60 to vascular endothelial cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Therefore, IS-741 may become useful for treating patients with severe acute pancreatitis and MOF. IS-741 has therapeutic effects on acute pancreatitis induced in the rat by using a closed duodenal loop, 10 and on lung injury in rats with cerulein-induced pancreatitis complicated by endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…7-9 IS-741 suppresses various inflammatory events, [7][8][9] and therefore might be clinically useful in treating severe acute pancreatitis and MOF. The present study examined the effect of short-term administration of IS-741 on ethionineinduced pancreatitis in rats as a model of acute necrotizing pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…14 There have been several studies suggesting that this new anti-inflammatory agent was effective for in-vivo animal inflammatory models. Yotsuya et al 16 reported that IS-741 (0.03 or 0.3mg/kg per h), administered subcutaneously in a rat severe acute pancreatitis model (induced by trypsin and taurocholic acid) could inhibit the development of the pancreatic lesion as well as the progression to multiple organ failure. Liang et al 17 reported that intravenous IS-741 (0.03mg/kg per h) administration for 30 min effectively prevented cerulein-induced pancreatitis and the associated lung injury following an endotoxin challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, there are only few reports about the efficacy of leukocyte-endothelial interaction inhibitors against intestinal inflammation. 19 In the present study, we investigated the effects of oral IS-741 on rat experimental ileitis.…”
mentioning
confidence: 99%